Molecular epidemiology of Mycobacterium tuberculosis in East Lancashire 2001–2009. Issue 8 (15th June 2011) - Sails, A D; Barrett, A; Sarginson, S; Magee, J G; Maynard, P; Hafeez, I; Ormerod, L P
Abstract : Background: East Lancashire has had high rates of tuberculosis for 40 years. The ethnically diverse population is predominantly of South Asian and white origin. Drug resistance data from 1960 to 1999 indirectly suggest that no significant inter-ethnic transmission has occurred. This study used mycobacterial interspersed repetitive unit variable number tandem repeat (MIRU-VNTR) fingerprinting to assess clustering within and between ethnic groups. Methods: All isolates of Mycobacterium tuberculosis from January 2001 to July 2009 from East Lancashire postcode areas were MIRU-VNTR fingerprinted. Clusters of strains with indistinguishable profiles were also assessed epidemiologically, and their MIRU-VNTR profiles compared with the UK M tuberculosis Strain Typing Database. Results: 332 strains were typed (63 white patients, and 269 non-white patients). 198 MIRU-VNTR profiles were identified, with 144 profiles occurring only once. The typing clustered 187 strains into 53 clusters indistinguishable at all 12 loci and these were further characterised using the exact tandem repeat loci A, B, and C. The 15 loci clustered 32/63 (50.8%) of white and 110/269 (40.9%) of non-white cases and all but nine clusters were of the same ethnicity. The nine inter-racial clusters were further assessed from an epidemiological and clinical perspective and fingerprinting using nine additional loci. Isolates within two of the clusters were further discriminated using the additional nine loci. However, the additional loci did not further discriminate the isolates in the other seven inter-racial clusters. Conclusions: MIRU-VNTR fingerprinting indicates that although there is evidence of a high rate of transmission within the South Asian sub-population, the data suggest that there is little inter-ethnic transmission.